Balancing state discretion and the rule of law: challenges, opportunities, and prospects in the era of digital governance - Vdovichen, Vitalii (Journal of Law and Political Scienes, 2025)
The purpose of the study is to study the theoretical foundations and practical approaches to the implementation of discretionary powers of state authorities and to find ways to improve control over its application. The study identified key problems in the implementation of discretion : the lack of clear boundaries and standards of application, an insufficient level of transparency, weakness of appeal mechanisms and risks of abuse in the digital environment. The best international practices are summarized, demonstrating the need to combine judicial control, preventive supervision and ethical self-regulation. The feasibility of introducing electronic databases of discretionary decisions in Ukraine, the creation of independent supervisory bodies and regulatory regulation of algorithmic management is substantiated. The practical significance of the results obtained lies in the possibility of using the proposed approaches to form a transparent and accountable model of public administration in accordance with European standards.
Keywords: discretion of state power; rule of law, public administration; judicial control; transparency; digitalization; ethical standard; algorithmic solutions